Two Case reports on Sickle Cell Disease: Presented with Pallor and recurrent Attacks of Bones and Joints Pain (Medicine Today, 2017)
Sickle cell disease is a hereditary hemolytic anaemia due to abnormal haemoglobin. Sickling of RBCs occurs due to abnormal hemoglobin which leads to vaso-occlusive crisis. The highest frequency of sickle cell disease is found in tropical regions, particularly in Sub-Saharan Africa, tribal regions of India and in Middle-East. Though sickle cell disease is not common in our country, recently we have two cases of sickle cell disease presented with fatigue and pallor with bones and joints pains. These cases were diagnosed by electrophoresis of hemoglobin, peripheral smear, Sickling test and relevant investigations. The most significant advance in the therapy of sickle cell anaemia is the introduction of Hydroxyurea to prevent acute chest syndrome, number of pain crisis, repeated transfusions and number of trips to hospital. Hydroxyurea is considered in first case (case no. 1) as he has frequent episodes of acute attack and recover well after blood transfusion. Case no.2 also a good candidate for Hydroxyurea but not given as his acute attack is less frequent and in close contact for further observation and evaluation.Medicine Today 2017 Vol.29(2): 51-54